The effects of resistance exercise training on macro- and micro-circulatory responses to feeding and skeletal muscle protein anabolism in older men - Phillips, Bethan E.; Atherton, Philip J.; Varadhan, Krishna; Limb, Marie C.; Wilkinson, Daniel J.; Sjøberg, Kim A.; Smith, Kenneth; Williams, John P. (Wiley, 2015)
The anabolic effects of dietary protein on skeletal muscle depend on adequate skeletal muscle perfusion, which is impaired in older people. This study explores fed state muscle microvascular blood flow, protein metabolism and exercise training status in older men. We measured leg blood flow (LBF), muscle microvascular blood volume (MBV) and muscle protein turnover under post-absorptive and fed state (i.v. Glamin to double amino acids, dextrose to sustain glucose ∼7–7.5 mmol l−1) conditions in two groups: 10 untrained men (72.3 ± 1.4 years; body mass index (BMI) 26.5 ± 1.15 kg m2) and 10 men who had undertaken 20 weeks of fully supervised, whole-body resistance exercise training (RET) (72.8 ± 1.4 years; BMI 26.3 ± 1.2 kg m2). We measured LBF by Doppler ultrasound and muscle MBV by contrast-enhanced ultrasound. Muscle protein synthesis (MPS) was measured using [1, 2-13C2] leucine with breakdown (MPB) and net protein balance (NPB) by ring-[D5] phenylalanine tracers. Plasma insulin was measured via ELISA and indices of anabolic signalling (e.g. Akt/mTORC1) by immunoblotting from muscle biopsies. Whereas older untrained men did not exhibit fed-state increases in LBF or MBV, the RET group exhibited increases in both LBF and MBV. Despite our hypothesis that enhanced fed-state circulatory responses would improve anabolic responses to nutrition, fed-state increases in MPS (∼50–75%; P < 0.001) were identical in both groups. Finally, whereas only the RET group exhibited fed-state suppression of MPB (∼–38%; P < 0.05), positive NPB achieved was similar in both groups. We conclude that RET enhances fed-state LBF and MBV and restores nutrient-dependent attenuation of MPB without robustly enhancing MPS or NPB.